2022
DOI: 10.2196/38172
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Physical Activity Levels and Associated Factors in Older US Women During the COVID-19 Pandemic: Cross-sectional Study

Abstract: Background Physical activity (PA) is vital for attenuating the aging-related physiological and functional declines in women aged 60 years or above. However, little is known about the objectively assessed PA behavior in older women during the COVID-19 pandemic and its association with sociodemographics, health and physical function, and COVID-19 related factors. Objective This study aims to examine the objectively measured PA levels and associated factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Prior research has shown that FOF is associated with reduced PA levels in community-dwelling older adults using objectively measured PA data ( Jefferis et al, 2014 ; Choudhury et al, 2022 ). Our results broadly agree with it, showing that total daily PA volume was significantly lower in two high FOF groups (i.e., irrational and congruent) than the rational group.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that FOF is associated with reduced PA levels in community-dwelling older adults using objectively measured PA data ( Jefferis et al, 2014 ; Choudhury et al, 2022 ). Our results broadly agree with it, showing that total daily PA volume was significantly lower in two high FOF groups (i.e., irrational and congruent) than the rational group.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our study findings, it can be conferred that PA interventions to promote healthy body composition and dynamic balance in older adults should integrate approaches to combine both LPA and MVPA recommendations. Since LPA already accounts for a substantial portion of older adults’ daily activities [ 54 ], increasing LPA might provide a feasible target for enhancing the daily balance between sedentary time and total PA (i.e., LPA + MVPA) among older adults, especially for those with chronic diseases and geriatric conditions. Additionally, in our current sample, inactive-high sedentary participants had the least favorable outcomes in body composition profile.…”
Section: Discussionmentioning
confidence: 99%
“…Details on each questionnaire and physical assessment are described in the following section. In addition, each individual was provided with a wrist-worn accelerometer and given instructions on how to wear it for 7 days [23]. The body composition was recorded using a portable bioelectrical impedance analysis device, and participants were instructed per the manufacturer's guidelines [5,24].…”
Section: Study Design and Participantsmentioning
confidence: 99%